Patent citations, university inventor patents, and survival in the German laser source industry (1960-2005) - Luis F. Medrano (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2012)
The relationship between innovation and firm survival is analyzed for the population of German laser source producers from the beginning of the industry until 2005. Innovation effort is approximated by the generation of high quality patents in laser sources technology (IPC H01S) and by having patents with university inventors. Quality patents are defined as those in the upper quartile of the strongly right-skewed distribution of forward citations. Having quality patents is positive and statistically significantly associated with firm survival. New firms without relevant capabilities inherited at their birth may be capable of compensating for their lack of adequate pre-entry experience with corresponding innovative behavior. Having patents with university inventors is apparently not related to firm survival.
Keywords: L25; M13; O30; O52; 330; firm survival; patent citations; quality patents; university-inventor patents; innovation; Laser; Optoelektronische Industrie; Innovation; Unternehmensentwicklung; Patent; Forschungskooperation; Deutschland